PENTINGNYA SOCIAL SUPPORT UNTUK MENINGKATKAN SUBJECTIVE WELL-BEING SANTRI PONDOK PESANTREN : A SYSTEMATIC LITERATURE REVIEW - Nindya, Aulia Rachma (IAIN Syaikh Abdurrahman Siddik Bangka Belitung, 2022)
The low subjective welfare of students living in boarding school dormitories can occur because of the lack of good social support. Santri who do not receive Social support have a tendency to be indifferent to others and be less polite, their emotional state is slightly more depressed, and lack academic achievement. This study aims to conduct a literature review on the application of Social support to improve subjective well-being conditions for students who live in boarding school dormitories. The results of the discussion show that assistance with Social support can affect students in adapting, having good social roles, good friendship relationships, increasing sense of independence, decreasing emotional pressure, so that they have good thoughts, behavior, and mental health in order to achieve subjective well-being conditions. more prosperous.